Myocardial Mechanical Dispersion Predicts Adverse Cardiac Remodeling in Patients with ST Segment Elevation Myocardial Infarction Who Underwent Primary Percutaneous Coronary Intervention - Petyunina, O.; Kopytsya, M.; Kobets, A.; Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2023)
Objective: The aim of the study was to investigate whether increased left ventricular mechanical dispersion is an early predictor for adverse cardiac remodeling in ST-segment elevation myocardial infarction patients who had post-percutaneous coronary intervention thrombolysis in myocardial infarction (TIMI) flow grade > 2. Methods: A total of 119 post-percutaneous coronary intervention ST elevation myocardial infarction patients with TIMI flow grade >2 were prospectively included in the study. Left ventricular global longitudinal strain was quantified by 2-dimensional speckletracking echocardiography, and left ventricular mechanical dispersion was determined at baseline and after 1 year to assess adverse cardiac remodeling. The levels of circulating biomarkers were measured at the baseline. TIMI score and the Global Registry of Acute Coronary Events score systems were used to evaluate the prognosis of patients. Results: Patients with high quartile versus low quartile of left ventricular mechanical dispersion exerted higher Global Registry of Acute Coronary Events and TIMI score grades, left ventricular end-systolic volume, global longitudinal strain, and levels of the N-terminal fragment of brain natriuretic peptide and lower left ventricular ejection fraction. Multivariate log regression showed that N-terminal fragment of brain natriuretic peptide > 953 pg/mL, global longitudinal strain > –8%, and high quartile of left ventricular mechanical dispersion remained independent predictors for adverse cardiac remodeling. Addition of left ventricular mechanical dispersion to the N-terminal fragment of brain natriuretic peptide improved the discriminative potency of the whole model. Conclusion: Measurement of left ventricular mechanical dispersion might be useful in determining the risk of adverse cardiac remodeling in post-percutaneous coronary intervention ST elevation myocardial infarction patients.
Keywords: Myocardial revascularization; percutaneous coronary intervention; acute coronary syndrome; cardiac function; heart failure